Immunogenicity of two doses of inactive COVID‐19 vaccine and third booster dose mRNA vaccine in patients with cancer receiving active systemic therapy. Issue 4 (23rd September 2022) - Guven, Deniz Can; Incesu, Fatma Gul Gulbahce; Yildirim, Hasan Cagri; Erul, Enes; Chalabiyev, Elvin; Aktas, Burak Yasin; Yuce, Deniz; Arik, Zafer; Kilickap, Saadettin; Aksoy, Sercan; Erman, Mustafa; Hayran, Kadir Mutlu; et al.
Abstract: We aimed to evaluate the seroconversion rates after two doses of inactive COVID‐19 vaccine (CoronaVac) and the benefit of a third dose mRNA vaccine booster in patients with cancer receiving active treatment. Patients with solid tumors receiving active treatment (n = 101) and patients with no‐cancer (n = 48) as the control group were included in the study. All the patients and controls had received two doses of CoronaVac and a third booster dose of the mRNA vaccine (Bnt162b2). Anti‐SARS‐CoV‐2 Spike Receptor Binding Domain IgG antibody levels after the second and third dose were measured with quantitative ELISA. The median age of the patients was 66 (IQR 60‐71). 79% of the patients were receiving chemotherapy, and 21% were receiving immunotherapy at the time of vaccination. Antibody levels measured after two doses of CoronaVac were significantly lower in patients with cancer than in the control group (median 0 μg/ml [IQR 0‐1.17 μg/ml] vs median 0.91 μg/ml [IQR 0‐2.24 μg/ml], respectively, P = .002). Seropositivity rates were 46.5% in patients with cancer and 72.9% in the control group ( P = .002). Antibody measurement was performed in 26 patients after the third dose. Seroconversion rate increased from 46.5% to 88.5% ( P < .001), and the antibody titers significantly increased with the third‐dose booster (median 0 μg/ml [IQR 0‐1.17 μg/ml] after two doses vs 12.6 μg/ml [IQR 1.8‐69.1 μg/ml] after third booster dose, P < .001). Immunogenicity of CoronaVac is low in patients with cancer receiving active treatment, and administering a third dose of an mRNA vaccine is effective in terms of improving seroconversion rates. Abstract : What's new? The existing data on the efficacy of inactive COVID‐19 vaccines and the benefit of heterologous boosters remains limited in patients with cancer, who may be immunocompromised by cancer itself or anti‐cancer treatments. This study shows that the immunogenicity of two doses of inactive COVID‐19 vaccine is lower in patients with cancer receiving active treatment compared with controls. Administering a third booster dose of an mRNA vaccine significantly improves seroconversion rates in these patients. The results could be important for clinical practice considering the limited access to mRNA vaccines in several parts of the world.